(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: The therapeutic use of the only Pancreatic Lipase (PL) - inhibiting anti-obesity drug available in clinical practice, orlistat, is bedevilled with unbearable side effects, necessitating the discovery of new and better-tolerated ones. Hibiscus sabdariffa, a folkloric anti-obesity plant is a plausible repertoire from which such agents could be sought. Objective: The main objective of this work was to evaluate in silico the phytochemicals of Hibiscus sabdariffa for a possible identification of potential leads for PL inhibitory anti-obesity drug discovery.. Methods: Phytoligands from H. sabdariffa were subjected to a series of in silico evaluations including site directed docking, MM/GBSA calculations, SwissADME drug-likeness screening, Protox II-based toxicity evaluations and a 20 ns molecular dynamics (MD) simulation. Results: MM/GBSA ranking of docked phytoligands and SwissADME evaluations produced three PL inhibitor hits. One of them, canthin-6-one, demonstrated minimal end-organ toxicity with a 1200 mg/kg LD50; its PL complex generated stability-implying root mean square deviation (RMSD), root mean square fluctuation (RMSF), radius of gyration (Rg) and solvent accessible surface area (SASA) plots, after the 20 ns MD simulation. Conclusion: Hibiscus sabdariffa-based canthin-6-one has demonstrated, in silico, high human PL binding affinity, impressive drug-likeness/toxicity profiles and stability-implying MD simulation parameters. It is therefore, herein, recommended as lead for further in vitro, in vivo and molecular modification studies for possible development into a clinical PL inhibitory anti-obesity drug.